Methodological Problems of Statistical Study of Regional Tourism and Tourist Expenditure - Ovcharov, Anton Olegovich (Economy of Regions, 2015)
The aim of the work is the analysis of the problems of regional tourism statistics. The subject of the research is the tourism expenditure, the specificity of their recording and modeling. The methods of statistical observation and factor analysis are used. The article shows the features and directions of statistical methodology of tourism. A brief review of international publications on statistical studies of tourist expenditure is made. It summarizes the data from different statistical forms and shows the positive and negative trends in the development of tourism in Russia. It is concluded that the tourist industry in Russia is focused on outbound tourism rather than on inbound or internal. The features of statistical accounting and statistical analysis of tourism expenditure in Russian and international statistics are described. To assess the level of development of regional tourism the necessity of use the coefficient of efficiency of tourism. The reasons of the prevalence of imports over exports of tourism services are revealed using the data of the balance of payments. This is due to the raw material orientation of Russian exports and low specific weight of the account “Services” in the structure of the balance of payments. The additive model is also proposed in the paper. It describes the influence of three factors on the changes in tourist expenditure. These factors are the number of trips, the cost of a trip and structural changes in destinations and travel purposes. On the basis of the data from 2012-2013 we estimate the force and the direction of the influence of each factor. Testing of the model showed that the increase in tourism exports caused by the combined positive impact of all three factors, chief of which is the growing number of foreigners who visited Russia during the concerned period.